Multi-feature supported dam height measurement method for large hydraulic projects using high resolution remote sensing imagery - Runsheng Ma; Yating Wei; Qiang Zhao; Shuangming Zhao; Zhiwen Yang; Fang Shangguan; Jixuan Li; Zhaowen Wu; Zhijuan Shen; Wen Zhang; Linyi Li; Lingkui Meng (International Journal of Applied Earth Observations and Geoinformation, 2024)
Most studies on building height estimation using remote sensing imagery mainly focus on urban buildings with relatively regular shape and relatively flat terrain, and pay little attention to large buildings with complex terrain like dams. A new dam height measurement method was proposed in this paper, which used shadow measurement data and metadata from multiple image sources. The method not only considers the geometric relationship between the sun, the satellite and the dam, but also considers the influence of the satellite zenith and introduces the correction factor, which brings the higher precision. Two dams with a maximum height of more than 200 m were studied, and the dam height is estimated by considering the topography around the dam and the shape of the dam. The experimental results show that the Mean Relative Error (MRE) of the estimated dam height using our proposed method are 3.1% and 4.7% for our two study areas, while the MRE of the traditional models is more than 13%. By doing so, we are able to calculate dam height and obtain information on temporal changes in dam height during the construction process, even in situations without a Digital Surface Model (DSM). Therefore, the proposed method will be propitious to the dynamic supervision of the construction process of the dams effectively.